The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1039/c7fo00602k
|View full text |Cite
|
Sign up to set email alerts
|

Dietary pectin and mango pulp effects on small intestinal enzyme activity levels and macronutrient digestion in grower pigs

Abstract: The effects of refined pectin and mango pulp on macronutrient digestion and small intestinal enzyme activity were studied in grower pigs. Diets based on wheat starch with and without apple pectin or dried mango fruit pulp were fed to 30 grower pigs for 21 days. Pigs were euthanized two hours postprandially, and their gastrointestinal contents recovered. Starch and protein digestion as well as α-amylase activity were all increased in pigs fed pectin. In contrast, fat digestion, lipase and protease (trypsin) act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Digestibility may also be determined by changes in digestive enzyme secretion. Our results suggested that activities of amylase is affected by viscosity rather than DF content, which is in agreement with the finding that soluble DF intake decreases macronutrient digestion by reducing digestive enzyme activities (23,48,49) . Nevertheless, previous in vitro and in vivo studies have shown different responses on the effect of viscosity on digestive enzyme activities.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Digestibility may also be determined by changes in digestive enzyme secretion. Our results suggested that activities of amylase is affected by viscosity rather than DF content, which is in agreement with the finding that soluble DF intake decreases macronutrient digestion by reducing digestive enzyme activities (23,48,49) . Nevertheless, previous in vitro and in vivo studies have shown different responses on the effect of viscosity on digestive enzyme activities.…”
Section: Discussionsupporting
confidence: 92%
“…Isaksson et al demonstrated that increased viscosity by adding pectin to jejunal juice of humans reduced activities of trypsin and amylase (48) . In contrast, the activities of amylase, protease, and lipase in the pancreas and on pancreatic-biliary secretion were increased in rats fed viscous guar gum for 14-d compared with control (51) , and increased amylase activity has been reported in pigs fed pectin for 21-d compared with those fed control diets (23) . Because of the very different models and compounds used in the literature, to define the effect of chyme viscosity on digestive enzymatic activity requires further research.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Diets based on wheat starch with and without apple pectin or dried mango fruit pulp were fed to 30 grower pigs for 21 days. The data suggests that pectin has a significant effect on digestive enzyme activity and subsequent influence on macronutrient digestion 40 .…”
Section: Introductionmentioning
confidence: 94%